High-temperature mass spectrometric study and modeling of thermodynamic properties in the La2O3-TiO2 system - Valentina L. Stolyarova; Andrey L. Shilov; Viktor A. Vorozhtcov; Sergey I. Lopatin; Anna V. Fedorova (Chemical Thermodynamics and Thermal Analysis)
The vapor composition over two samples of the La2O3-TiO2 system containing 50 and 90 mole % TiO2 was explored by the high-temperature Knudsen effusion mass spectrometric method. TiO2, TiO, and LaO species were identified in the vapor. From the measured partial pressures of the vapor species, the TiO2 activity as a function of composition was determined at the temperatures of 2290 K and 2475 K. As a result of modeling within the generalized lattice theory of associated solutions, the La2O3 activity was determined. The obtained component activities and the excess Gibbs energy indicate strong negative deviations from the ideal behavior, which are illustrated by the calculated concentration dependence of the relative number of mixed bonds in the system under study.